Group A β-Haemolytic Streptococcus Infection Presenting with Sore Throat at Paediatric OPD - Gurung, R; Budhathoki, S; Amatya, R; Poudyal, N; Shrestha, S; Baral, R (Health Renaissance, 2011)
Objective: To study the prevalence of streptococcal pharyngitis in pediatric patients presenting with sore throat. Methods: A total of 100 patients aged 5.15 years were enrolled in the study. Verbal consent was obtained to collect specimens. The specimens were collected with the help of sterile cotton tipped swab, cultured in blood agar and chocolate agar as per the guideline. Streptococcus pyogenes was identified on the basis of Gram.s stain and its sensitivity towards 0.04 units of bacitracin disc. Antimicrobial susceptibility testing of the isolates was performed using Kirby Bauer disc diffusion method. Finding: Out of 100 patients which were included, 54 were male and 46 were female. GAS was isolated from 5 patients, of which 3 were male and 2 were female. Of the 5, S. pyogenes strains isolated, 2(66.6%) were found to be resistant to cotrimoxazole. Ciprofloxacin resistance was seen in one isolate. No resistance was detected in gentamycin, cefalexin, penicillin, and erythromycin. Conclusion: The results show that the prevalence of streptococcal pharyngitis is 5% among OPD cases, further study should be conducted in the community to know the actual prevalence of streptococcal pharyngitis. Keywords: Pharyngitis; Prevalence; Streptococcus pyogenes DOI: 10.3126/hren.v8i2.4418 Health Renaissance, May-Aug 2010; Vol 8 (No.2):90-92